Thank you for the opportunity to help you with your question!

they two solution imaginary solution :

X1 = (12 - isqrt(1044))/(-18)

X2 = (12 + isqrt(1044))/(-18)

wait me 30 min , i will come to give you the detailed answer ok

just a few minute

i will show you the work on a picture of a paper ; just wait i wiill give me camera

sorry my camera broken:

(3/(x+1)) - (3/2) = (6/(3x+3))

so :

(3/(x+1)) - (6/(3x+3)) - (3/2)= 0

(3/(x+1)) - (2/(x+1))- (3/2)= 0

(1/(x+1))- (3/2)= 0

((2 - 3x - 3)/(2x+2)) = 0

((- 3x - 1)/(2x+2)) = 0

((- 3x - 1) = 0

3x + 1 = 0

x = -1/3

if you don't understand please just ask , the solution that's i gave you was note correcte

i am glad to work with you each time y ou have any other exercise just invite me i will give you the detailed answer

Good luck

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up